Blending Online Digital Tools in Low Resourced Classrooms in Nepal - Sapkota, Ashok (Journal of NELTA Gandaki, 2020)
The wider uses of digital online tools have been explicitly practised in the educational spheres including access and use of technology in Nepal during the pandemic situation, like COVID 19. This article focuses on the use of six different digital online tools which could be effectively blended in face-to-face and distance classroom teaching by teacher educators to reshape the way they teach. It links the idea of tech integration along technological, pedagogical and content knowledge (TPACK) model in the use of technology. The data elicited from the narratives of ten experienced teacher educators relate the grassroots challenges in the use of tech tools to foster the professional identity of teachers. It further discusses the effective use of digital online tools even in the difficult circumstances minimizing the challenges and digital divide.